2013
DOI: 10.1002/cbdv.201300286
|View full text |Cite
|
Sign up to set email alerts
|

5α‐Androst‐16‐en‐3α‐ol βD‐Glucuronide, Precursor of 5α‐Androst‐16‐en‐3α‐ol in Human Sweat

Abstract: 5α-Androst-16-en-3α-ol (α-androstenol) is an important contributor to human axilla sweat odor. It is assumed that α-andostenol is excreted from the apocrine glands via a H2 O-soluble conjugate, and this precursor was formally characterized in this study for the first time in human sweat. The possible H2 O-soluble precursors, sulfate and glucuronide derivatives, were synthesized as analytical standards, i.e., α-androstenol, β-androstenol sulfates, 5α-androsta-5,16-dien-3β-ol (β-androstadienol) sulfate, α-andros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…B 375: 20190269 array of minor acids, are linked to a glutamine (Gln) residue [10,11]. The sulfur compounds are secreted as part of a cysteine-glycine (Cys-Gly) dipeptide [20], and the steroid 5-α-androst-16-en-3α-ol was detected as a glucuronide conjugate in axilla secretions [21]. Such conjugates are well known from liver metabolism and toxicology: many acids are conjugated to Gln prior to secretion in the kidney, electrophilic chemicals are conjugated to glutathione and then secreted as Cys or Cys-Gly conjugates and many alcohols are linked to glucuronic acid to render them hydrophilic prior to secretion (e.g.…”
Section: Odourant Precursorsmentioning
confidence: 99%
“…B 375: 20190269 array of minor acids, are linked to a glutamine (Gln) residue [10,11]. The sulfur compounds are secreted as part of a cysteine-glycine (Cys-Gly) dipeptide [20], and the steroid 5-α-androst-16-en-3α-ol was detected as a glucuronide conjugate in axilla secretions [21]. Such conjugates are well known from liver metabolism and toxicology: many acids are conjugated to Gln prior to secretion in the kidney, electrophilic chemicals are conjugated to glutathione and then secreted as Cys or Cys-Gly conjugates and many alcohols are linked to glucuronic acid to render them hydrophilic prior to secretion (e.g.…”
Section: Odourant Precursorsmentioning
confidence: 99%
“…Recent studies have demonstrated that some soluble odourless compounds are secreted by apocrine glands and some are unique to the human species [ 25 ]. These soluble compounds are transformed by the microbiota to release odorant carboxylic acids, sulfur compounds and odorant steroids [ 20 - 22 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides fermentation, odor molecules in the secondary metabolites can be produced via the gene activation or secretion systems of various microorganisms in the skin. Both C. acnes and S. warneri have the β-glucuronidase activities to increase androstenol (5alpha-Androst-16en-3alpha-ol) in sweat odors (21). Corynebacterium spp.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that Corynebacterium spp. can produce VFAs, HMHA, 3M2H, and 5α-androst-16-en-3α-ol (21,33,36). Anaerococcus spp.…”
Section: Discussionmentioning
confidence: 99%